Radial distribution functions and thermodynamics of macroparticles in dusty plasmas (International Journal of Mathematics and Physics, 2013)
Starting from the previously developed pseudopotential model of dust particles interaction in the plasma,which takes into account both the finite-size and the screening effects, equilibrium distribution functionsarewellstudied. Consideration is entirely based on the renormalization theory of plasma particles interaction which results inthe so-called generalized Poisson-Boltzmann equation. The main idea is to apply the renormalization theory in orderto treat the dust grains as a one component plasma with a specific interaction potential. The interaction potentialderived in such a way does naturallyincorporate the number density of dust particles and can be utilized for furthertheoretical considerations. Such an approach provides quite effectivecalculation scheme for the radial distributionfunction of the dust particles whosenon-monotonic behavior is observed at different values of plasma parameters toprove short-range or even long-range order formation in the system. The correlation energy is investigated in a widerange of plasma parameters and the results are examined from the viewpoint of the thermodynamic stability.